The role of home gardens in promoting multi-functional agriculture in Hungary - Birol, Ekin; Bela, György; Smale, Melinda (Wiley, 2005)
Home gardens are small‐scale family farms managed with traditional methods. Throughout Hungary's history, they have provided food security and diet quality to families who have faced volatile food prices and fluctuating real incomes. If markets function better with European Union (EU) accession, the conditions for reliance on home gardens may weaken—although not for all Hungarians. This paper reports the results of an interdisciplinary project investigating the economic value of home gardens of over 400 farmers in rural Hungary. We find that home gardens generate several public goods, including agro biodiversity and cultural heritage. The most economically, geographically and ecologically marginalized farmers not only manage the home gardens with the highest levels of public goods, but also derive the highest private benefits from them. Should Hungary seek to promote multi functional agriculture in line with the objectives of the EU's reformed Common Agricultural Policy, then provisions for home gardens would need to be incorporated into national programmes and legal frameworks. This research identifies some of the crops and the characteristics of farmers and farming communities that would constitute least cost targets for related programmes. Findings have implications for other EU member Central and Eastern European Countries with similar traditions of home gardening.